2004
DOI: 10.1177/107110070402500202
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Calcaneal Fractures: Operative Versus Nonoperative Treatment

Abstract: Other than demonstrating a slightly more depressed Bohler's angle, patients sustaining bilateral calcaneal fractures are very similar to those in whom the injury is confined to one side. The evidence presented here does not definitively support primary operative intervention for bilateral calcaneal fractures. Neither objective nor subjective functional outcomes are significantly improved following such intervention. However, careful operative patient selection will minimize complications and lessen the need fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 24 publications
2
26
0
4
Order By: Relevance
“…Surgeons usually rely on visual and radiographic evaluation to assess anatomic reduction and achievement of good subtalar motion when determining the accuracy of their surgical reduction. Buckley et al [19][20][21] and others 22 reported better functional results and less pain when Böhler angle restoration and anatomic reduction were achieved. On the other hand, Ibrahim et al 23 and Kennedy et al 24 found no association between radiographically measured restoration of the angle and clinical outcome.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Surgeons usually rely on visual and radiographic evaluation to assess anatomic reduction and achievement of good subtalar motion when determining the accuracy of their surgical reduction. Buckley et al [19][20][21] and others 22 reported better functional results and less pain when Böhler angle restoration and anatomic reduction were achieved. On the other hand, Ibrahim et al 23 and Kennedy et al 24 found no association between radiographically measured restoration of the angle and clinical outcome.…”
Section: Discussionmentioning
confidence: 95%
“…This agrees with the findings of a recent meta-analysis of current evidence by Jiang et al 13 and a Cochrane report by Bridgman et al 11 . Other investigators 19,20,22 found better VAS pain scores only in certain subgroups, such as patients with no residual subtalar displacement or those who did not receive Workers' Compensation. The mean VAS pain score in the present study also improved slightly at eight to twelve years of follow-up compared with one year.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, clinical outcomes frequently correlate with particular ranges for preoperative or post-operative BA [7,[14][15][16]. The propagation of reporting BA through the literature has been supported by reports showing its good inter-observer reliability.…”
Section: Introductionmentioning
confidence: 93%
“…Many authors [1][2][3][4][5][6][7][8] have attempted to define algorithms for conservative and surgical treatments of calcaneal fractures depending on articular involvement and the degree of displacement. Despite several comparative studies between conservative and surgical methods have been carried out [3,9], the management of intra-articular calcaneal fractures remains controversial.…”
Section: Introductionmentioning
confidence: 99%